2004
DOI: 10.1111/j.1432-1033.2004.04381.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of shark and other vertebrate DNases I

Abstract: We purified pancreatic deoxyribonuclease I (DNase I) from the shark Heterodontus japonicus using three‐step column chromatography. Although its enzymatic properties resembled those of other vertebrate DNases I, shark DNase I was unique in being a basic protein. Full‐length cDNAs encoding the DNases I of two shark species, H. japonicus and Triakis scyllia, were constructed from their total pancreatic RNAs using RACE. Nucleotide sequence analyses revealed two structural alterations unique to shark enzymes: subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…2) 28 , it is plausible that the insertion of a few amino acid residues or deletion of one residue in the loop region might have little effect on the overall structure of the protein, thus preserving the activity. We have previously demonstrated that hydrophobicity and α-helical structure in the signal sequence region of vertebrate DNase I proteins affect the level of expressed enzyme activity via the post-translational protein targeting pathway 31 . It can be assumed that the deletion corresponding to p.delLeu10_Ala12 would reduce the hydrophobicity and α-helical structure in the signal sequence region, thus diminishing the DNase I activity to about 30% that of the wild type.…”
Section: Resultsmentioning
confidence: 99%
“…2) 28 , it is plausible that the insertion of a few amino acid residues or deletion of one residue in the loop region might have little effect on the overall structure of the protein, thus preserving the activity. We have previously demonstrated that hydrophobicity and α-helical structure in the signal sequence region of vertebrate DNase I proteins affect the level of expressed enzyme activity via the post-translational protein targeting pathway 31 . It can be assumed that the deletion corresponding to p.delLeu10_Ala12 would reduce the hydrophobicity and α-helical structure in the signal sequence region, thus diminishing the DNase I activity to about 30% that of the wild type.…”
Section: Resultsmentioning
confidence: 99%
“…Co‐translational targeting of a protein to the endoplasmic reticulum is initiated when a signal recognition particle binds to a hydrophobic signal sequence at the N‐terminus of the nascent chain, and the common physico‐chemical properties of this sequence, including the hydrophobicity of the central core, are essential for its function . Previously, we have demonstrated that alterations in the signal sequence could affect the expression level of the corresponding expression construct inserted with vertebrate DNase I in the transfected cells . It could be assumed that a reduction in the hydrophobicity of the signal sequence through replacement of Ala by Asp at position 20 corresponding to p.Ala20Asp may decrease its function as a co‐translational targeting signal, resulting in a 0.50‐fold reduction of the DNase 1L2 activity of the A20D construct relative to that of the wild‐type enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…It remains unknown why both DNases disappeared during the evolution of Protostomia from the predicted ancestral species of Eumatazoa, in contrast to Deuterostomia. Next, multiple alignment analysis of the amino acid sequences of DNase I and 1L3 from Animalia organisms available on the genome database, in addition to vertebrate DNases I determined previously [21][22][23][24], was performed; DNase I and 1L3 derived from 40 and 26 species, respectively, were analyzed (Figs S1 and S2). Among the amino acid sequences of animal DNases I, all the organisms fully conserved 27 amino acid residues, which included the four amino acid residues responsible for the active site [25] and two Cys residues that form the disulfide bond responsible for structural stability of the enzyme [26], corresponding to Glu100, His156, Asp234 and His274, and the Cys residues at positions 195 and 231 in human DNase I, respectively.…”
Section: Multiple Alignment Analysis Of the Amino Acid Sequences Of Amentioning
confidence: 99%